Development of assays using hexokinase and phosphoglucomutase gene sequences that distinguish strains of Leishmania tropica from different zymodemes and microsatellite clusters and their application to Palestinian foci of cutaneous leishmaniasis. - Kifaya Azmi; Gabriele Schonian; Lionel F Schnur; Abedelmajeed Nasereddin; Suheir Ereqat; Ziad Abdeen (Public Library of Science (PLoS), 2013)
BACKGROUND/OBJECTIVES: Palestinian strains of L.tropica characterized by multilocus enzyme electrophoresis (MLEE) fall into two zymodemes, either MON-137 or MON-307. METHODOLOGY/PRINCIPLE FINDINGS: Assays employing PCR and subsequent RFLP were applied to sequences found in the Hexokinase (HK) gene, an enzyme that is not used in MLEE, and the Phosphoglucomutase (PGM) gene, an enzyme that is used for MLEE, to see if they would facilitate consigning local strains of L.tropica to either zymodeme MON-137 or zymodeme MON-307. Following amplification and subsequent double digestion with the restriction endonucleases MboI and HaeIII, variation in the restriction patterns of the sequence from the HK gene distinguished strains of L.tropica, L.major and L.infantum and also exposed two genotypes (G) among the strains of L.tropica: HK-LtG1, associated with strains of L.tropica of the zymodemes MON-137 and MON-265, and HK-LtG2, associated with strains of L.tropica of the zymodemes MON-307, MON-288, MON-275 and MON-54. Following amplification and subsequent digestion by the restriction endonuclease MboI, variation in the sequence from the PGM gene also exposed two genotypes among the strains of L.tropica: PGM-G1, associated only with strains of L.tropica of the zymodeme MON-137; and PGM-G2, associated with strains of L.tropica of the zymodemes MON-265, MON-307, MON-288, MON-275 and MON-54, and, also, with six strains of L.major, five of L.infantum and one of L.donovani. The use of the HK and PGM gene sequences enabled distinction the L.tropica strains of the zymodeme MON-137 from those of the zymodeme MON-265. This genotyping system 'correctly' identified reference strains of L.tropica of known zymodemal affiliation and also from clinical samples, with a level of sensitivity down to <1 fg in the case of the former and to 1 pg of DNA in the case of the latter. CONCLUSIONS/SIGNIFICANCE: Both assays proved useful for identifying leishmanial parasites in clinical samples without resource to culture and MLEE.